Pedagogical Projecting of the Model of a Future Specialist - Oleksandr Mozolev (Pedagogical Discourse, 2018)
Training future specialist to professional activity is one of the main tasks of higher and professional education. Pedagogical modeling of professional activity is used to determine the content of quantitative and qualitative information, which is necessary for modern researchers to further work, and also directs them to the prospects of career growth.The purpose of the article is to analyse the content of the process of pedagogical projecting of the model of the future specialist. The author established requirements for the training of qualified personnel determine the necessary competences which specialist has to master, his professionally important qualities, necessary in future activity, and also carry out the goal setting of the training process, acquiring the necessary knowledge and skills. It is identified that the competence of future specialists is a set of their competencies, which in turn are classified into key required, without exception to all graduates and professional, appropriate to the particular specialty.The article reveals the content of constructing a model of the future specialist which allows to solve such problems: a description of the specialist's work in the course of its professional activities; identifying inconsistencies between the content of training and specific professional activities of specialists. Requirements are defined as quality standards to the training of future qualified personnel. The list of basic competencies of the future specialist has been set which include: general cultural, methodological, professionally-oriented. The model of the specialist personality is characterized. Disclosed the content of the process modeling of learning outcomes and the algorithm of its development is determined. The definition of the concept «pedagogical design» was offered to reveal the principles and forms of pedagogical design.It is established that pedagogical design is one of the most common types of research. It is considered as an alternative to the classroom system in educational institutions. Project technology should be used as a supplement to other forms of direct or indirect learning as a means of accelerated professional growth of the individual.